Isolation, Characterization, and In vitro Antioxidant Activity of Arjunolic Acid from Arjuna Bark (Asian Journal of Pharmaceutics (AJP), 2026)
The aim of the present investigation is to study the Isolation, Characterization, and in vitro AntioxidantActivity of Arjunolic Acid from Arjuna Bark. Materials and Methods: Fresh bark of Terminalia arjunawas collected from a natural habitat and authenticated by a qualified taxonomist. Powdered bark (1 kg) wasdefatted using petroleum ether (60–80°C) in a Soxhlet apparatus for 8 h. The defatted marc was extracted withmethanol for 48 h. The extract was filtered and concentrated under reduced pressure using a rotary evaporatorto obtain a crude methanolic extract. The ethyl acetate fraction was adsorbed onto silica gel and subjected tocolumn chromatography using silica gel (60–120 mesh) as stationary phase and Chloroform: Methanol mixtures(95:5 → 80:20) as a Elution System. Fractions were monitored by thin layer chromatography (TLC) usingchloroform: Methanol (9:1). Fractions showing identical spots were pooled and recrystallized using methanolto yield white crystalline arjunolic acid. Arjunolic acid was dissolved in methanol to obtain concentrations of10, 25, 50, 75, and 100 μg/mL. Ascorbic acid was used as a reference standard at the same concentrations. The2,2-diphenyl-1-picrylhydrazyl (DPPH) assay was performed according to the method described earlier. Briefly,1 mL of 0.1 mM DPPH solution was mixed with 1 mL of arjunolic acid at different concentrations. The mixturewas incubated in the dark for 30 min and absorbance was measured at 517 nm. Results: High-performance TLCwas performed using silica gel 60 F254 plates and a mobile phase of Toluene: Ethyl acetate: Methanol: Formicacid (6.5: 3.0: 0.5: 0.1 v/v/v/v). Both standard and isolated arjunolic acid exhibited a single compact band at Rf≈ 0.45–0.46 after derivatization. Densitometric scanning at 540 nm confirmed peak overlap, verifying compoundidentity. Conclusion: The isolated arjunolic acid can serve as a reference marker for standardization and furtherpharmacological evaluation. The in vitro antioxidant evaluation confirmed that arjunolic acid possesses significantfree radical scavenging and reducing properties.